INFLUENCE OF HEARING AIDS ON ACADEMIC PERFORMANCE OF LEARNERS WITH DISABILITY IN PUBLIC PRIMARY SCHOOLS IN SABOTI SUB-COUNTY, KENYA - Njofu, Peter Namasaka; Kikechi, Ronald Werunga (IJRDO - Journal of Social Science and Humanities Research, 2022)
The purpose of this study was to assess the influence of hearing aids on academic performance of learners with disability in public primary schools in Saboti sub-county, Kenya. The study adopted a descriptive survey research design with a target population of 1509, which comprised of 1496 learners with disability in public primary schools in Saboti sub-county and 13 head teachers. A sample size of 310 was determined by the use of Krejcie and Morgan Table for determining sample sizes. Purposive and stratified random sampling techniques were utilized to determine the respondents. From the sample size of 310, all the 13 head teachers were purposively selected to participate in the study, with the remaining 297 being learners with disability, who were picked through stratified random sampling technique. The main data collection tools used in the study were, interview schedules and structured questionnaires. A reliability coefficient of 0.79 was obtained from the instrument, indicating that they were reliable. Descriptive statistics and chi-square test was employed to analyze quantitative data and presented in tables. The analysis of qualitative data was as per the themes of the study and was presented using quotations. The study established that hearing aids such as microphones, amplifiers, and receivers helped in improving academic performance. The study will be beneficial to scholars, legislators and society as a whole